The effect of heavy rainfall on the exposure risks of sedimentary phthalate esters to aquatic organisms. (March 2022) - Chen, Chih-Feng; Ju, Yun-Ru; Lim, Yee Cheng; Wang, Ming-Huang; Patel, Anil Kumar; Singhania, Reeta Rani; Chen, Chiu-Wen; Dong, Cheng-Di
Abstract: Phthalate esters (PAEs) have known widely being used in plastic products leading to being ubiquitous in the environment by easy to release from those products. This study aims to understand the impact of heavy rainfall on the concentration of PAEs in surface sediments of the Salt River in Kaohsiung, Taiwan, and its potential ecological risks on aquatic organisms. The potential ecological risk assessment of sediment PAEs is based on the total risk quotient (TRQ) method. The total concentration of 10 PAEs (∑PAE10) in sediments of the Salt River is 333–13, 615 ng/g dw, with an average of 4212 ± 3753 ng/g dw. Before the rainy season, the ∑PAE10 concentration in sediments at the outlets of domestic sewage in upstream was 9768–13, 615 ng/g dw, which were relatively higher than other sites (542–3721 ng/g dw). During the rainy season, the ∑PAE10 concentration was 2820–12, 041 ng/g dw, which was 1–11 times higher than that determined before the rainy season. After the rainy season, the ∑PAE10 concentration recorded was 530–6652 ng/g dw, which is 1–11 times lower than the value obtained during the rainy season. PAEs in sediments of the Salt River may have low to moderate potential risks to algae, crustaceans, and fish. Bis(2-ethylhexyl) phthalate (DEHP) and diisobutyl phthalate (DiBP) are the main PAE that poses a potential risk to algae and crustaceans, and to fish respectively, whose values of risk quotient accounts for 40–69% of the TRQ value. The distribution of TRQ values for these aquatic organisms show a decreasing trend of PAEs level with respect to the rainy season: during the rainy season > after the rainy season > before the rainy season. Heavy rainfall may cause more serious pollution in sediments and increase the exposure risk of PAEs to aquatic organisms. Graphical abstract: Image 1 Highlights: Long-chain PAEs as plasticizers are the dominant PAEs in the surface sediments. PAEs in sediments may mainly come from the release of plastic products in daily life. Heavy rainfall may increase the exposed risk of PAEs to aquatic organisms. DEHP and DiBP are the main PAEs that pose potential risks to aquatic organisms.